New resilient survival model for Malaysian small and medium-sized enterprises during and post-crisis of COVID-19 / Dr. Mohamad Hanif Abu Hassan, Dr. Wahidah Shari and Dr. Zuraidah Mohamed Isa - Abu Hassan, Mohamad Hanif; Shari, Wahidah; Mohamed Isa, Zuraidah (Universiti Teknologi MARA, Kedah, 2022)
When something unpredictable causes confusion, the concerns can be disastrous not only for Malaysian small and medium-sized enterprises (SMEs) but also for the country's economic structure. In this regard, how can SMEs survive after a crisis period caused by the COVID-19 pandemic? The study aims to develop a resilient survival model towards ensuring the continuity of SMEs during and after a crisis. The study will apply quantitative and qualitative approaches, via questionnaire distribution and focus group discussion with an expert. Based on the comprehensive review of previous literature and supported by the theory of contingency, a conceptual framework will be developed with some potential variables, such as leadership characteristics, organizational operations, dynamic capabilities and information technology, which can help SMEs to survive this crisis. The proposed conceptual model can be useful for policymakers, small business owners and managers, to understand how the coordination of identified initiatives can play an important role in surviving this crisis. The study will also provide recommendations for small businesses on ways to stay competitive through resilience strategies. This study hopes to contribute to existing crisis management literature by identifying strategies for SME survival and resilience, specifically in developing regions during periods of prolonged crises.